Union character and social class: a study of white-collar unionism - Blackburn, R. M. (London, Batsford, 1967)
This is a study of the importance of union character in the unionization of white-collar workers. As such it is intended as a contribution to the general theoretical understanding of trade unionism, while adding, in particular, to our knowledge of the increasingly important field of white-collar unionism
includes index
Bibliography: p. [281]-288.
occ 17/01/2019
Loans
Keywords: Labor unions; Bank employees